Story Book Development With Local Culture Content As Learning Companion For 5th Grade Primary Students - Laksmi, Ni Luh Ayu Nitya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to develop children's storybooks supported with local culture as learning companion to continue previous prototype by Kharisma (2017). Method use ADDIE (Analysis, Design, Development, Implementation, Evaluation) which is two first stages already done. Subjects in this study were 2 experts, 2 teachers and 25 students of fifth grade. Development, the process of making the story, and produce a story book entitled